MAKTAB O’QUVCHILARINI ROBOTOTEXNIKA VA SUN’IY INTELLEKT ISHLANMALARIGA JALB QILISHNING AHAMIYATI - Abdullayeva Rahimajon; Davletboyev Sardorbek (Ustozlar uchun, 2025)
Currently, the fields of robotics and artificial intelligence (AI) are developing rapidly and are becoming one of the most in-demand areas in the global labor market. By involving schoolchildren in these areas and providing them with practical experience, it is possible to form future IT specialists. This thesis analyzes the effectiveness of websites and platforms specially designed for students, their impact on education, and development prospects.